APLIKASI KAMUS BAHASA DAERAH MAKASSAR BERBASIS MOBILE - Kurnia Yahya (P3M STMIK Profesional Makassar, 2021)
This research is develop a mobile-based digital dictionary application for Indonesian to regional languages of the four ethnic groups of South Sulawesi. The benefit of this research is make it easier for users to quickly add vocabulary, especially the four ethnic languages in the South Sulawesi province, especially Bugis, Mandar, Toraja and Makassar languages quickly. The research method used in this research is String Matching. This method will search for words that match those entered by the user and the platform used is eclipse.